Cheaper by the dozen 2 - Shankman, Adam (Pasig City : Viva Video, 2006)
Steve Martin is funnier than ever in this hilarious sequel! Tom Baker (Steve Martin) and wife Kate (Bonnie Hunt) bring their clan together for a memorable summer getaway. But their dream vacation turns into an outrageous competition with the overachieving, overzealous family of Tom's long-time rival, Jimmy Murtaugh (Eugene Levy). Featuring all the original Baker kids, including Hillary Duff, Tom Welling and Piper Perabo, this supersized comedy is fun for the whole family!